(untitled) (Bangladesh Journal of Bioethics, 2018)
In the face of the recent backlashes against homosexual persons in Africa, on the ground that the phenomenon is un-African and/or threat to procreation and marital values, it is pertinent to review the discourse in the light of how ancient Africans perceived the reality. This is imperative given the lack of consensus on the part of scientists to disinter a conclusive finding on what causes homosexual behaviours among humans. In this research, I employ traditional Yorùbá philosophy to provide a plausible justification for homosexuality among the people. In the face of this justification via Yorùbá folklore, I find that there is no documented evidence among the ancient Yorùbá that is suggestive of discrimination and stigmatization of homosexuals and inter-sex persons. As homosexual persons were respected but not criminalized, this study recommends the regurgitation of this outlook in the contemporaneous dealings with homosexual persons, beginning with the repealing of the Same-Sex Marriage Prohibition Act of 2014 in Nigeria, which is inconsistent with African values and outlooks on the subject.